“Let’s say it wears an Ebola Coat, but it’s not Ebola”: The Rhetoric and Politics of Reframing a Vaccine for a Transnational Clinical Trial - Thiongane, Oumy; Bamba, Issiaka; Sawadogo, Hélène N; David, Pierre-Marie; Mathiot, Benjamin; Graham, Janice E (Anthropologica, 2024)
Focusing on how disease, health and vaccine research take on different forms, meanings and interpretations in diverse contexts, we examine the use of rhetoric to recruit people living with HIV in sub-Saharan Africa for an Ebola vaccine clinical trial. Conducted after the West African Ebola outbreak in a country that had not been affected by Ebola, the urgency, relevance and materiality of disease, health and biomedical research takes on different shapes, meanings and understandings. The limitations of multilateral initiatives to address inequalities in associated healthcare and access to essential medicines and vaccines highlight the tensions created when neither local researchers nor patient communities have been involved in the design or planning of the trial, and when the pathologies targeted by experimental technologies are either inappropriate for the people they are aimed at, or unfold without the knowledge of a social consensus. By deciphering the metaphorical discourse on an Ebola vaccine candidate and the erasure of a viral ontology from the hybrid technology to which it gives rise, we understand that the discourse of clinic staff makes it possible to establish a scientific truth in the service of instrumental productivity: manufacturing consent and recruiting arms for vaccine shots. In this article, we show that the closure of biomedicine to an esoteric discourse reflects the weakness of science in communicating what it actually does and the techniques it produces. It also addresses the failure of community engagement in the field of emerging infectious diseases.